2012
DOI: 10.1128/mcb.06525-11
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for Activation of the Atypical AGC Kinase Greatwall during M Phase Entry

Abstract: The atypical AGC kinase Greatwall (Gwl) mediates a pathway that prevents the precocious removal of phosphorylations added to target proteins by M phase-promoting factor (MPF); Gwl is thus essential for M phase entry and maintenance. Gwl itself is activated by M phase-specific phosphorylations that are investigated here. Many phosphorylations are nonessential, being located within a long nonconserved region, any part of which can be deleted without effect. Using mass spectrometry and mutagenesis, we have identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
145
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(150 citation statements)
references
References 48 publications
(82 reference statements)
4
145
1
Order By: Relevance
“…To mimic mitotic exit, Cdk1 was inactivated by the addition of roscovitine. As expected, Cdk1 inhibition resulted in fast and efficient dephosphorylation of Cdc27 and XErp1 (lane [3][4][5][6][7][8]. Collectively, these experiments validate Xenopus embryonic extract as an appropriate system to analyze mitotic exit.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…To mimic mitotic exit, Cdk1 was inactivated by the addition of roscovitine. As expected, Cdk1 inhibition resulted in fast and efficient dephosphorylation of Cdc27 and XErp1 (lane [3][4][5][6][7][8]. Collectively, these experiments validate Xenopus embryonic extract as an appropriate system to analyze mitotic exit.…”
Section: Resultssupporting
confidence: 77%
“…At mitotic entry, Cdk1/cyclin B mediates the inactivation of PP2A-B55 via the atypical AGC-type kinase Greatwall (Gwl) [6,7]. According to the current model [8,9], Cdk1/cyclin B phosphorylates Xenopus Gwl at T193 and T206 and these phosphorylations enable Gwl to autophosphorylate itself at a C-terminal serine residue (S883) resulting in Gwl activation. Active Gwl phosphorylates Arpp19 and the closely related endosulfine a/Ensa (collectively referred to as Arpp19) and thereby converts them into potent inhibitors of PP2A-B55 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Gwl is phosphorylated in Mphase, in quantitative correlation with its kinase activity. 11,12 Mitotic phosphorylation of Gwl by MPF within its presumptive activation loop is required for Gwl activation, suggesting that MPF acts upstream of Gwl during mitotic entry. [11][12][13] It has also been shown that Gwl can be phosphorylated by Plk1, whereas the specific function and regulation of this modification remains to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Mitotic phosphorylation of Gwl by MPF within its presumptive activation loop is required for Gwl activation, suggesting that MPF acts upstream of Gwl during mitotic entry. [11][12][13] It has also been shown that Gwl can be phosphorylated by Plk1, whereas the specific function and regulation of this modification remains to be further clarified. 11,[13][14][15] In the search for new regulators of Gwl, our proteomic analysis revealed 2 groups of proteins as the major binding partners of Gwl which were co-purified with Gwl from G2 and M phase Xenopus oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…During M phase, MPF activates another mitotic kinase called Greatwall (Gwl) (Fig. 1) (28,36,37), and one function of Gwl is to phosphorylate and activate two phosphatase inhibitors, Ensa and Arpp19 (27,30). (In our model, we lump together Ensa and Arpp19 in a single variable, called ENSA.)…”
Section: Resultsmentioning
confidence: 99%